The moderating role of individual variables in the relationship between organizational justice and organizational commitment - Minibas-Poussard, Jale; Le Roy, Jeanne; Erkmen, Turhan (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - The purpose of this paper is to analyze the role of individual variables (organization-based self-esteem (OBSE) and work locus of control (WLOC)) that have been suspected to intervene as moderators on the relationship between organizational justice and organizational commitment. Design/methodology/approach - Self-administered survey was completed by 272 bank employees in Istanbul, Turkey. Findings - The results of moderation analyses clearly indicated a significant effect of OBSE and WLOC on the link between justice perceptions and organizational commitment. People are more committed to organizations when they have high OBSE. WLOC together with OBSE moderated the relationship between procedural justice and organizational commitment: people engaged less in their organizations when they perceived low procedural justice and reported lower OBSE. This relationship was revealed only when external WLOC scores were high. Research limitations/implications - The study was conducted in Istanbul, Turkey and the sample was limited to 272 participants. These results show that managers should not only hire personnel with high OBSE but they also should provide a participative work atmosphere where employees can perform with all their potential and capacity that may help them reveal their internal WLOC. Theoretical and practical implications of the study are discussed in the end. Originality/value - The study provides some valuable contributions to the existing body of literature by exhibiting the role of individual variables in the strong relationship between organizational justice and organizational commitment. The
Keywords: Quantitative; Organizational justice; Organization-based self-esteem; Organizational commitment; Work locus of control; CORE SELF-EVALUATIONS; JOB-SATISFACTION; SOCIAL-EXCHANGE; NORMATIVE COMMITMENT; DISTRIBUTIVE JUSTICE; ESTEEM; WORK; PERFORMANCE; LOCUS; ANTECEDENTS; Business & Economics; Psychology